DINAMIKA DALANG PEREMPUAN WAYANG PURWA DALAM ARUS ISLAMISASI - Budi Harianto; Seli Muna Ardiani (UIN Sayyid Ali Rahmatullah Tulungagung, 2018)
The female Wayang Purwa puppeteer originally came with a heavy Javanese cultural identity. This identity is reflected in the mindset of Javanese people who always move upward to achieve the principle of natural harmony; then practiced in specific rites in order to maintain the principle of unity. This important role then gradually declines over time. The process of Islamization which has strengthened after the reformation era has become an obstacle of the fate of female puppeteer. Female puppeteers are also the target of the current Islamization in the interests of political contestation in Indonesia. In addition to being confronted with the fact of malesentrism, the female puppeteers are also forced to accept a far more closed interpretation of Islamic religion. This article aims to answer how the dynamics that occur in female puppeteers of Wayang Purwa in the stream of Islamization. Keywords: Female Puppeteer, Cultural Identity, Islamization, Javanese Society Dalang perempuan wayang purwa mulanya hadir dengan identitas kultural Jawa yang kental. Identitas ini tercermin dalam pola pikir masyarakat Jawa yang selalu bergerak ke atas untuk mencapai prinsip harmoni alam; kemudian dipraktikkan dalam ritus-ritus khas demi menjaga prinsip kemenyatuan tersebut. Peran penting ini kemudian berangsur luruh dari waktu ke waktu. Arus Islamisasi yang kian menguat paska reformasi menjadi salah satu ‘pengganjal’ nasib dalang perempuan. Dalang perempuan juga menjadi sasaran arus Islamisasi dalam kepentingan kontestasi politik di Indonesia. Selain dihadapkan dengan fakta pedalangan yang malesentrism, dalang perempuan juga terpaksa mengamini tafsir keagamaan Islam yang jauh lebih tertutup. Artikel di bawah ini berusaha untuk menjawab bagaimana dinamika yang terjadi pada dalang perempuan wayang purwa dalam arus Islamisasi. Kata kunci: Dalang Perempuan, Identitas Kultural, Islamisasi, Masyarakat Jawa